A Problem-Driven User Experience Model for Evaluating Government Transparency Platforms: Evidence from A Regional Command Center - Yuniarto, Dwi; Subiyakto, A'ang; Rahman, Aedah Binti Abd. (Indonesian Scientific Journal, 2026)
The rapid expansion of digital transparency initiatives has encouraged local governments to adopt data-driven platforms to enhance public accountability. However, many transparency platforms struggle to achieve sustained public engagement due to unresolved user experience issues. This study proposes and empirically validates a problem-driven user experience evaluation model for government transparency platforms by focusing on three UX problem dimensions: Extra Time or Effort, Unexpected Experience, and Evolving Limitations. Using survey data from 147 valid users of the Command Center website of Sumedang Regency collected between October and December 2025, the model was tested using Partial Least Squares Structural Equation Modeling. The results indicate that all three UX problem dimensions significantly influence user experience satisfaction and continued intention to use, both directly and indirectly, with satisfaction acting as a partial mediator. The findings demonstrate that reducing cognitive effort, ensuring experiential consistency, and addressing systemic limitations are critical for sustaining public engagement with transparency platforms. This study contributes to the e-government and UX literature by offering a problem-oriented evaluation framework that emphasizes structural usability frictions rather than interface aesthetics, providing actionable insights for improving digital governance and public transparency.